A population survey of the glucose-6-phosphate dehydrogenase (G6PD) 563C>T (Mediterranean) mutation in Afghanistan. - Natsuda Jamornthanyawat; Ghulam R Awab; Naowarat Tanomsing; Sasithon Pukrittayakamee; Fazel Yamin; Arjen M Dondorp; Nicholas P J Day; Nicholas J White; Charles J Woodrow; Mallika Imwong (PLoS ONE)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a common inherited enzyme defect and an important problem in areas with Plasmodium vivax infection because of the risk of haemolysis following administration of primaquine to treat the liver forms of the parasite. We undertook a genotypic survey of 713 male individuals across nine provinces of Afghanistan in which malaria is found, four in the north and five in the east. RFLP typing at nucleotide position 563 detected 40 individuals with the Mediterranean mutation 563C>T, an overall prevalence of 5.6%. This varied according to self-reported ethnicity, with prevalence in the Pashtun/Pashai group of 33/369 (8.9%) compared to 7/344 individuals in the rest of the population (2.0%; p<0.001, Chi-squared test). Multivariate analysis of ethnicity and geographical location indicated an adjusted odds ratio of 3.50 (95% CI 1.36-9.02) for the Pashtun/Pashai group, while location showed only a trend towards higher prevalence in eastern provinces (adjusted odds ratio = 1.73, 0.73-4.13). Testing of known polymorphic markers (1311C>T in exon 11, and C93T in intron XI) in a subset of 82 individuals wild-type at C563 revealed a mixture of 3 haplotypes in the background population and was consistent with data from the 1000 Genomes Project and published studies. By comparison individuals with G6PD deficiency showed a highly skewed haplotype distribution, with 95% showing the CT haplotype, a finding consistent with relatively recent appearance and positive selection of the Mediterranean variant in Afghanistan. Overall, the data confirm that the Mediterranean variant of G6PD is common in many ethnic groups in Afghanistan, indicating that screening for G6PD deficiency is required in all individuals before radical treatment of P. vivax with primaquine.